2021
DOI: 10.1016/j.toxrep.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus derived mycotoxins in food and the environment: Prevalence, detection, and toxicity

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 249 publications
(257 reference statements)
0
67
0
4
Order By: Relevance
“…Some fungal isolates from industrial meat products are able, under particular environmental conditions and substrates, to produce mycotoxins such as aflatoxins or ochratoxins [10,[52][53][54] which have a serious toxic effect on human and animal health. In addition, the fungal species isolated in this study can also be a possible causal agents for human diseases such as pulmonary, skin mycosis, otomycosis, etc., [12,55].…”
Section: Discussionmentioning
confidence: 99%
“…Some fungal isolates from industrial meat products are able, under particular environmental conditions and substrates, to produce mycotoxins such as aflatoxins or ochratoxins [10,[52][53][54] which have a serious toxic effect on human and animal health. In addition, the fungal species isolated in this study can also be a possible causal agents for human diseases such as pulmonary, skin mycosis, otomycosis, etc., [12,55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SAD, an Aspergillus -, Penicillium - or Claviceps purpurea -derived mycotoxin [ 45 ], was detected in both years, with a higher average content in 2012 than in 2013. A higher risk of SAD contamination was recorded for N overload conditions (>300 kg N ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPA is a mycotoxin that is produced by Aspergillus and Penicillium ( Le Bars, 1979 ; Trucksess et al, 1987 ; Lin et al, 2009 ; Ostry et al, 2018 ; Rao et al, 2021 ). Even though CPA has been detected in a number of food sources such as peanuts, wheat, sunflower, meat, milk, and cheese, few studies have reported CPA as a mycotoxin because of its benign toxicity and low levels ( Urano et al, 1992 ; Dorner et al, 1994 ; Burdock and Flamm, 2000 ; Oliveira et al, 2006 ; Rao et al, 2021 ). In addition, CPA has not been considered chronically toxic, and it does not affect the immune system ( Burdock and Flamm, 2000 ; King et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%